Yeast oral vaccines against infectious diseases - Austriaco, Nicanor (Frontiers in Microbiology, 2023)
Vaccines that are delivered orally have several advantages over their counterparts that are administered via injection. Despite the advantages of oral delivery, however, approved oral vaccines are currently limited either to diseases that affect the gastrointestinal tract or to pathogens that have a crucial life cycle stage in the gut. Moreover, all of the approved oral vaccines for these disease involve live-attenuated or inactivated pathogens. This mini-review summarizes the potential and challenges of yeast oral vaccine delivery systems for animal and human infectious diseases. These delivery systems utilize whole yeast recombinant cells that are consumed orally to transport candidate antigens to the immune system of the gut. We begin with a discussion of the challenges associated with oral administration of vaccines and the distinct benefits offered by whole yeast delivery systems over other delivery systems. It then surveys the emerging yeast oral vaccines that have been developed over the past decade to combat animal and human diseases. In recent years, several candidate vaccines have emerged that can elicit the necessary immune response to provide significant protection against challenge by pathogen. They serve as proof of principle to show that yeast oral vaccines hold much promise.